Solving linear and non-linear stiﬀ system of ordinary diﬀerential equations by multistage adomian decomposition method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Hosen, Md Alal (2015)
In this paper, linear and non-linear stiﬀ systems of ordinary diﬀerential equations are solved by the classical Adomian decomposition method (ADM) and the multistage Adomian decomposition method (MADM). The MADM is a technique adapted from the standard Adomian decomposition method (ADM) where standard ADM is converted into a hybrid numeric-analytic method called the multistage ADM (MADM). The MADM is tested for several examples. Comparisons with an explicit Runge-Kutta-type method (RK) and the classical ADM demonstrate the limitations of ADM and promising capability of the MADM for solving stiﬀ initial value problems (IVPs).